ENGLISH AND UZBEK NEWSPAPER HEADLINES: A COMPARATIVE PRAGMATIC STUDY - G. Mirzayeva; D. Qurbonmuratova (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article studies pragmatic features of English and Uzbek newspaper headlines. The article focuses on brevity, source marking, numbers, evaluation, and the way a headline guides the reader’s interpretation before the article is read. The material includes a small comparative corpus of recent headlines from Reuters, The Guardian, and Gazeta. uz, and Xalq So’zi, supported by earlier headline research. Comparative analysis, pragmatic analysis, and close discourse reading are used in the study. The analysis shows that English headlines often rely on stronger compression, contrast, and short attention signals, while Uzbek headlines often place more explanation and institutional framing inside the headline line itself. Both traditions use numbers, authority, and cause-and-effect wording to create trust and urgency. The article may be useful for comparative pragmatics, media studies, translation, and classroom work with authentic news language.